Phosphorylation of lamins determine their structural properties and signaling functions - Torvaldson, Elin (Nucleus, 2015)
Lamin A/C is part of the nuclear lamina, a meshwork of intermediate filaments underlying the inner nuclear membrane. The lamin network is anchoring a complex set of structural and linker proteins and is either directly or through partner proteins also associated or interacting with a number of signaling protein and transcription factors. During mitosis the nuclear lamina is dissociated by well established phosphorylation- dependent mechanisms. A-type lamins are, however, also phosphorylated during interphase. A recent study identified 20 interphase phosphorylation sites on lamin A/C and explored their functions related to lamin dynamics; movements, localization and solubility. Here we discuss these findings in the light of lamin functions in health and disease.